Polyethylene Glycol-Mediated Synthesis of Cubic Iron Oxide Nanoparticles with High Heating Power - Iacovita, Cristian (Nanoscale Res Lett, 2015)
Iron oxide magnetic nanoparticles (IOMNPs) have been successfully synthesized by means of solvothermal reduction method employing polyethylene glycol (PEG200) as a solvent. The as-synthesized IOMNPs are poly-dispersed, highly crystalline, and exhibit a cubic shape. The size of IOMNPs is strongly dependent on the reaction time and the ration between the amount of magnetic precursor and PEG200 used in the synthesis method. At low magnetic precursor/PEG200 ratio, the cubic IOMNPs coexist with polyhedral IOMNPs. The structure and morphology of the IOMNPs were thoroughly investigated by using a wide range of techniques: TEM, XRD, XPS, FTIR, and RAMAN. XPS analysis showed that the IOMNPs comprise a crystalline magnetite core bearing on the outer surface functional groups from PEG200 and acetate. The presence of physisorbed PEG200 on the IOMNP surface is faintly detected through FT-IR spectroscopy. The surface of IOMNPs undergoes oxidation into maghemite as proven by RAMAN spectroscopy and the occurrence of satellite peaks in the Fe2p XP spectra. The magnetic studies performed on powder show that the blocking temperature (T(B)) of IOMNPs is around 300 K displaying a coercive field in between 160 and 170 Oe. Below the T(B), the field-cooled (FC) curves turn concave and describe a plateau indicating that strong magnetic dipole-dipole interactions are manifested in between IOMNPs. The specific absorption rate (SAR) values increase with decreasing nanoparticle concentrations for the IOMNPs dispersed in water. The SAR dependence on the applied magnetic field, studied up to magnetic field amplitude of 60 kA/m, presents a sigmoid shape with saturation values up to 1700 W/g. By dispersing the IOMNPs in PEG600 (liquid) and PEG1000 (solid), it was found that the SAR values decrease by 50 or 75 %, indicating that the Brownian friction within the solvent was the main contributor to the heating power of IOMNPs. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s11671-015-1091-0) contains supplementary material, which is available to authorized users.